Acute Reversal of Endothelial Dysfunction in the Elderly After Antioxidant Consumption - Wray, D. Walter; Nishiyama, Steven K.; Harris, Ryan A.; Zhao, Jia; McDaniel, John; Fjeldstad, Anette S.; Witman, Melissa A.H.; Ives, Stephen J.; Barrett-OʼKeefe, Zachary; Richardson, Russell S. (Hypertension (Dallas, Tex. 1979), 2012)
Aging is associated with a pro-oxidant state and a decline in endothelial function. Whether acute, enteral antioxidant treatment can reverse this decrement in vascular function is not well known. Flow-mediated vasodilation and reactive hyperemia were evaluated after consumption of either placebo or an oral antioxidant cocktail (vitamin C, 1000 mg; vitamin E, 600 IU; α-lipoic acid, 600 mg) in 87 healthy volunteers (42 young25±1 years; 45 older71±1 years) using a double-blind, crossover design. Blood velocity and brachial artery diameter (ultrasound Doppler) were assessed before and after 5-minute forearm circulatory arrest. Serum markers of lipid peroxidation, total antioxidant capacity, endogenous antioxidant activity, and vitamin C were assayed, and plasma nitrate, nitrite, and 3-nitrotyrosine were determined. In the placebo trial, an age-related reduction in brachial artery vasodilation was evident (young7.4±0.6%; older5.2±0.4%). After antioxidant consumption, flow-mediated vasodilation improved in older subjects (placebo5.2±0.4%; antioxidant8.2±0.6%) but declined in the young (placebo7.4±0.6%; antioxidant5.8±0.6%). Reactive hyperemia was reduced with age, but antioxidant administration did not alter the response in either group. Together, these data demonstrate that antioxidant consumption acutely restores endothelial function in the elderly while disrupting normal endothelium-dependent vasodilation in the young and suggest that this age-related impairment is attributed, at least in part, to free radicals.